Associations Between Marker Gene Alleles and Doe Traits in Nubian (Zaraibi) Goats in Egypt - Marai, F M; Fandoud, E i Abou; Daader, A H; Ela, A A Abu (Annals of Arid Zone, 2016)
Plasma proteins of Nubian goat does’ blood were examined for biochemical polymorphism of Immunoglobulin M (IgM), Immunoglobulin G (IgG), Immunoglobulin P (lgP), Albumin (A), I-Antitrypsin (AnLT), Carbonic Anhydrase Erythrocytes (C.An.Er), Trypsinogen Pancreas (T.P) and Trypsin Inhibitor (Tr.I) by using one-dimensional sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE), with high molecular weight protein standards as reference bands. Analysis of the results revealed the existence of association bet’;,ieen reproductive traits of homozygous Nubian doe genotypes and marker gene alleles. The lowest values of age at first kidding was associated with the allele Cb of C.An.Er marker gene, abortion in does with the allele pC of IgP and mortality rate with the allele pb of IgP The results also showed that the highest values of each of litter size and litter weight at birth and at weaning were associated with the allele Ia of Tr.1 marker gene and those of kilograms of kids produced/life time of doe at birth and at weaning (the latter parameter, i.e., kilograms of kids produced/life time of doe at weaning shows the final output of the traits: prolificacy, milk yield and pre-weaning mortality) with the allele Aa of A marker gene, Effects of the mentioned marker genes on the studied traits were found to be, in general. significant (P<O.OI or 0.05). Such positive results may suggest that marker-assisted selection could be carried out at a very early age on marker genotypes for improvement of Nubian goat traits, since such marker genotypes could be scored at very early ages.